2006
DOI: 10.1007/s10709-005-5537-7
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal patterns for longevity, fecundity and senescence in Drosophila buzzatii

Abstract: We tested for variation in longevity, senescence rate and early fecundity of Drosophila buzzatii along an elevational transect in Argentina, using laboratory-reared flies in laboratory tests performed to avoid extrinsic mortality. At 25 degrees C, females from lowland populations lived longer and had a lower demographic rate of senescence than females from highland populations. Minimal instead of maximal temperature at the sites of origin of population best predicted this cline. A very different pattern was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 61 publications
4
43
0
Order By: Relevance
“…D. koepferae is much shorter lived than D. buzzatii not only under standardized laboratory conditions (i.e., common environment, with experimentally removed extrinsic causes of mortality) but also in the wild (Sambucetti et al 2005). In addition, early fecundity is strongly higher in D. koepferae than in D. buzzatii during the first 6 days of age, whereas the opposite pattern of inter-specific variation is found for late fecundity particularly after 11 days of age in all populations studied (Sambucetti et al 2005;Norry et al 2006). In the present study we found that D. koepferae is much more resistant to heat knockdown than D. buzzatii in relatively early but not in later ages.…”
Section: Discussionmentioning
confidence: 93%
“…D. koepferae is much shorter lived than D. buzzatii not only under standardized laboratory conditions (i.e., common environment, with experimentally removed extrinsic causes of mortality) but also in the wild (Sambucetti et al 2005). In addition, early fecundity is strongly higher in D. koepferae than in D. buzzatii during the first 6 days of age, whereas the opposite pattern of inter-specific variation is found for late fecundity particularly after 11 days of age in all populations studied (Sambucetti et al 2005;Norry et al 2006). In the present study we found that D. koepferae is much more resistant to heat knockdown than D. buzzatii in relatively early but not in later ages.…”
Section: Discussionmentioning
confidence: 93%
“…Increased adult survival with elevation has been observed in fruit flies (Duyck et al 2010) and is explained by trade-offs between fecundity and longevity (Norry et al 2006) or increasing rates of damage from by-products of metabolism in hot temperatures (Leiser et al 2011). In annual species, however, selection on reproductive schedules may induce the opposite patterns, with accelerated senescence at the completion of reproduction (Tatar et al 1997).…”
Section: Insects and Other Arthropodsmentioning
confidence: 99%
“…It is not surprising that sex influences the lifespan extending effect of hormesis in insects as longevity in males and females respond differently to most genetic or environmental interventions (see, e.g. Maklakov et al 2008Maklakov et al , 2009Bilde et al 2009;Iliadi et al 2009;Tricoire et al 2009) and is even reported to respond differently to clinal selection in the wild (Norry et al 2006). However, in some experiments the hormesis phenomenon has been documented in both sexes (Le Bourg et al 2001;Hercus et al 2003).…”
Section: Introductionmentioning
confidence: 99%